2002
DOI: 10.1046/j.1365-3040.2002.00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of putative high‐affinity phosphate transporters in Chinese winter wheats

Abstract: China's soils tend to be phosphate deficient. Application of phosphorus fertilisers to the soil is yield and cost ineffective as much of the phosphate applied is rapidly locked-in and is inaccessible to the crop. Chinese Institutes have established intensive wheat breeding programmes to generate wheat varieties that produce adequate yields and grain quality in such soils. Three such wheat cultivars have been identified with good performance characteristics in the field. These three cultivars are thought to har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 33 publications
1
51
0
1
Order By: Relevance
“…However, in solution culture high P uptake efficiency can only depend on root architecture and the density of Pi transporters. Under field conditions, Lovrin 10 has been identified as more efficient than Jing 411 in P uptake and utilization (Davies et al, 2002). In the present hydroponic study, irrespective of external As concentrations, there were no significant differences in root biomass between the two cultivars ( Fig.…”
Section: Analysis Of Variancementioning
confidence: 51%
See 2 more Smart Citations
“…However, in solution culture high P uptake efficiency can only depend on root architecture and the density of Pi transporters. Under field conditions, Lovrin 10 has been identified as more efficient than Jing 411 in P uptake and utilization (Davies et al, 2002). In the present hydroponic study, irrespective of external As concentrations, there were no significant differences in root biomass between the two cultivars ( Fig.…”
Section: Analysis Of Variancementioning
confidence: 51%
“…Under field conditions, the wheat cultivar Lovrin 10 has been identified as more efficient than cultivar Jing 411 in P uptake and utilization (Davies et al, 2002). In wheat, several Pi transporters have been identified and the expression pattern of phosphate transporters differs between these two cultivars (Davies et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the functions of HvPHT1;3 and HvPHT1;4 in Pi homeostasis are not clear. Only one wheat PHT1 gene, TaPHT1;2D1, has been characterized so far (Miao et al, 2009), although several TaPHT1 genes are reported (Davies et al, 2002;Miao et al, 2009). Whole genomic sequences of barley and wheat are not yet available, which has hindered progress toward the functional characterization of PHT1 genes and their regulation in barley and wheat.…”
mentioning
confidence: 99%
“…It would be worthwhile for previous studies, with data already available, to repeat the QTL analysis based upon relative yield, and compare the results with those previously published. In China, several P-efficient wheat varieties were identified by extensive screening of germplasm at high and low soil-P; the sole criterion for efficiency was relative yield, irrespective of the yield potential of the variety (Davies et al 2002).…”
Section: Genetics Of Puementioning
confidence: 99%